2015
DOI: 10.1093/jac/dkv433
|View full text |Cite
|
Sign up to set email alerts
|

Any impact of blips and low-level viraemia episodes among HIV-infected patients with sustained virological suppression on ART?

Abstract: Blips are frequent (22.7%) among HIV-infected patients with sustained virological suppression on ART. HIV patients with blips and at least three consecutive detected, but not quantified, HIV-RNA determinations (<20 copies/mL) had a higher risk of VF. These findings highlight the relevance of maintaining HIV-RNA levels below the limits of quantification of current assays (<20 copies/mL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
32
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 17 publications
0
32
0
1
Order By: Relevance
“…In United States and some other resource-rich countries [10][11][12], LLV is defined as a VL between 50 and 200 copies/ml according to the Department of Health and Human Services (DHHS) guidelines (USA, 2016) [13]. In Europe and most resource-rich settings [14,15], LLV is defined as a VL between 20 and 50 copies/ml, according to the European acquired immune deficiency syndrome (AIDS) Clinical Society (EACS) guidelines [16]. Although LLV frequently occurs during treatment, none of the guidelines suggest changing the treatment regimen or intensifying treatment in case of LLV.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In United States and some other resource-rich countries [10][11][12], LLV is defined as a VL between 50 and 200 copies/ml according to the Department of Health and Human Services (DHHS) guidelines (USA, 2016) [13]. In Europe and most resource-rich settings [14,15], LLV is defined as a VL between 20 and 50 copies/ml, according to the European acquired immune deficiency syndrome (AIDS) Clinical Society (EACS) guidelines [16]. Although LLV frequently occurs during treatment, none of the guidelines suggest changing the treatment regimen or intensifying treatment in case of LLV.…”
Section: Introductionmentioning
confidence: 99%
“…An earlier national observational cohort study from USA found that an LLV above 400 copies/ml could not predict AIDS or death [17]. However, multiple recent cohort studies worldwide demonstrated that the level of LLV is a determinant of prognosis; high level of LLV (> 200 copies/ml) occurring only once might increase the risk of virologic failure (VF) [7,14,18]. Some studies from developed countries found that persistent LLV or frequently occurring LLV of 50-200 copies/ml also increased the risk of VF [6,19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In United States and some other resource-rich countries 10-12 , LLV is defined as a VL between 50-200 copies/ml according to the Department of Health and Human Services (DHHS) guidelines (USA, 2016) 13 . In Europe and most resource-rich settings 14,15 , LLV is defined as a VL between 20-50 copies/ml, according to the European acquired immune deficiency syndrome (AIDS) Clinical Society (EACS) guidelines 16 . Although LLV frequently occurs during treatment, none of the guidelines suggest changing the treatment regimen or intensifying treatment in case of LLV.…”
mentioning
confidence: 99%
“…An earlier national observational cohort study from USA found that an LLV above 400 copies/ml could not predict AIDS or death 17 . However, multiple recent cohort studies worldwide demonstrated that the level of LLV is a determinant of prognosis; high level of LLV (> 200 copies/ml) occurring only once might increase the risk of virologic failure (VF) 7, 14,18 . Some studies from developed countries found that persistent LLV or frequently occurring LLV of 50-200 copies/ml also increased the risk of VF 6, 19,20 .…”
mentioning
confidence: 99%